“Diseño e implementación de un sistema de gestión en Seguridad y Salud Ocupacional para el aserradero moderno ubicado en la ciudad de Riobamba” - Rodríguez Llerena, Marco Vinicio (2017)
The objective of this research is to design a management system about occupational health and safety for the “Modern sawmill”, company dedicated to the first transformation of wood that comes from forest exploitation in order to respond to the demands and pressures of the regulatory entity and to ensure a safe working environment. The method applied was the deductive based on the general knowledge such as: safety occupational, health, identification, measurement, evaluation and risk factor in order to determine the degree of evolution of the system and their elements. According to the analysis the risk factors to which the workers are exposed are: Physicists, chemists, mechanical and psychosocial, among them, noise, with an averaged about 95.9 dB (A), it is considered one of the most dangerous risks in the wood industry and organic dust in suspension (PM2.5 - PM10), it presents a greater degree of exposure in the area where the machine is located. The problems identified in the company are the lack of policies on security and occupational health the problems identified in the company are the lack of policies on health and occupational safety in addition of an improper control of system documentation which gives us an efficiency index of 18.71% As a result of this project, an efficiency index of 91.41% is obtained reflecting a very significant advance in occupational health and safety. It established a system of control to the observations made for a constant review by the management and a more efficient analysis of the obtained data, achieving a more pragmatic and ideal system for the modern sawmill.